Land Rezoning and Structural Transformation in Rural India: Evidence from the Industrial Areas Program. (28th February 2021) - Blakeslee, David; Chaurey, Ritam; Fishman, Ram; Malik, Samreen
Abstract: Zoning laws that restrict rural land to agricultural production pose an important institutional barrier to industrial development. We study the effects of the Industrial Areas (IA) program in Karnataka, India, which rezoned agricultural land for industrial use, but without the economic incentives common with other place-based policies. We find that the program caused a large increase in firm creation and employment in villages overlapping the IAs. Moreover, the surrounding areas experienced spillover effects, with workers shifting from agricultural to non-agricultural employment, and entrepreneurs establishing numerous small-scale service sector and agricultural firms.